STRATEGI SOFT BALANCING INDIA DALAM PEMBLOKIRAN APLIKASI CINA - Ahmad Mudhofarul Baqi (Indonesian Journal of International Relations, 2022)
This article aims to explain why India has banned 267 Chinese application amidst the escalation of the Ladakh border dispute. Rely on seconder data with explanative type research and adopt soft-balancing concept from T.V Paul about economic sanction and Robert A. Pape regarding economic strengthen. The results show that the Chinese apps banned are India's soft-balancing strategy toward China. Soft-Balancing strategy driven by capability disparity among India and China economically, military, and technologically. Soft-balancing strategy open the room for strengthening the Indian apps ecosystem. Strengthen the Indian apps Ecosystem through a recommendation of Indian apps to substitute the function of Chinese apps, held Digital India AatmaNirbhar Bharat Innovate Challenge to Indian apps developer, and launched AatmaNirbhar Bharat apps to support the self-reliance of Indian apps ecosystem.